Olfactory dysfunction: properties of the Sniffin' Sticks Screening 12 test and associations with quality of life. - Hinz, A.; Luck, T.; Riedel-Heller, S. G.; Herzberg, P. Y.; Rolffs, C.; Wirkner, K.; Engel, C. (Eur Arch Otorhinolaryngol, 2019)
PURPOSE: The Sniffin' Sticks Screening 12 test is a test of olfactory performance based on pen-like odor dispensing devices. The aims of this study were to analyze the performance of this test in a general population sample and to explore associations between olfactory dysfunction and quality of life. METHODS: A large community sample (n = 7267) completed the Sniffin' Sticks Screening 12 test and several questionnaires measuring quality of life, anxiety, dispositional optimism, social support, and satisfaction with life. RESULTS: According to the criteria recommended by the test manufacturer, 5.1% of the participants were anosmic (score </= 6), 52.4% were dysosmic (7 </= score </= 10), and 42.5% were normosmic (score >/= 11). While frequencies of correct identification differed between the 12 sticks, all sticks contributed positively to the test results. The associations between olfactory functioning and quality of life variables were negligible. In the multivariate analyses, none of the associations reached the 1% significance level. CONCLUSIONS: While studies with patients in otorhinolaryngological clinics often report substantial detriments to their quality of life in relation to olfactory dysfunction, the present epidemiological study cannot confirm this association for the general population.
Keywords: Adult; Aged; Anxiety; Female; Humans; Male; Middle Aged; Odorants; Olfaction Disorders/*diagnosis/*psychology; Personal Satisfaction; *Quality of Life; Social Support